Comparison of body mass index, anti-citrullinated peptides antibodies status and periodontal condition in first degree relatives individuals to rheumatoid arthritis (2016)
Association studies in rheumatoid arthritis (RA) have been focused in the pre-clinical phases of the disease in asymptomatic individuals with higher risk to develop RA such as first-degree relatives (FDR). Previous data has shown that obesity, the anti-citrullinated peptides antibodies (ACPA) status and the periodontal condition may modulate the severity and the clinical presentation of RA. The objective of this study were to investigate the body mass index (BMI), ACPA status, the frequency and severity of periodontal disease and the level of antibodies IgG-1, IGG-2 against P. gingivalis in healthy FDR individuals of RA-patients and compare these variables with a control group of healthy individuals from general population.